Citizenship Education: The Perceptions of Social Studies Omani Student Teachers - Saif N. AlMaamari; Ian Menter (Sultan Qaboos University, 2013)
The purpose of this study was to investigate the perceptions of Omani student-teachers of social studies major about citizenship and citizenship education. Interviews were used to achieve this purpose. Ten students participated in the study: 5 females and 5 males. Data were analyzed qualitatively using analytic induction and interpretive analytic framework. Qualitative results show a wide range of interesting views on citizenship that highlighted the influence of the social, cultural and political context in shaping the meaning of citizenship and citizenship education. The results from interviews can be classified into five categories: (a) Citizenship is a multi-faceted concept; (b) Citizenship education is a crucial area in the school curriculum; (c) social studies is still the main approach of introducing citizenship education; (d) citizenship education is an area which is missing in teacher preparation programs and (e) Citizenship education is practiced to an extent in practical training programs.